2022
DOI: 10.3390/diagnostics12122922
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent Optical Fluctuation Flowmetry: A New Method for the Assessment of Foot Perfusion in Patients with Diabetes-Related Lower-Extremity Complications

Abstract: (1) Background: To date, there are no studies evaluating the ability of the incoherent optical fluctuation flowmetry (IOFF) method to assess foot tissue perfusion. The aim of this study was to evaluate the correlation between perfusion values measured by IOFF and TcPO2 in patients with diabetes-related lower-extremity complications. (2) Methods: This was an observational, cross-sectional, two-center study. Diabetic patients with peripheral artery disease and/or diabetic foot ulcers were studied (n = 27, examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Other methods based on the use of biophotonic techniques are also known for diagnosing the state of microcirculatory function in DM. For example, in the studies by Dremin et al [48] and Glazkova et al [54], LDF was used in conjunction with the local heating test, which resulted in sensitivity and specificity values of up to 0.92 and 0.90 respectively, and AUC values of up to 0.94. Evaluation of blood volume fraction and skin blood oxygenation simultaneously with measurement of the polarisation index of light reflected from the skin resulted in a sensitivity of 0.95 and specificity of 0.85 [55].…”
Section: B Logistic Regression Based Predictive Modellingmentioning
confidence: 99%
“…Other methods based on the use of biophotonic techniques are also known for diagnosing the state of microcirculatory function in DM. For example, in the studies by Dremin et al [48] and Glazkova et al [54], LDF was used in conjunction with the local heating test, which resulted in sensitivity and specificity values of up to 0.92 and 0.90 respectively, and AUC values of up to 0.94. Evaluation of blood volume fraction and skin blood oxygenation simultaneously with measurement of the polarisation index of light reflected from the skin resulted in a sensitivity of 0.95 and specificity of 0.85 [55].…”
Section: B Logistic Regression Based Predictive Modellingmentioning
confidence: 99%
“…The authors concluded that the lens of women and people of color had a higher attenuation during DECT, which may indicate a higher density or increased calcium concentration and a high probability of cataract formation. P. Glazkova et al studied the possibilities of incoherent optical fluctuation flowmetry (IOFF) to analyze the perfusion of foot tissues in patients with diabetes mellitus [23]. Perfusion in foot tissues was also assessed using transcutaneous oxygen pressure measurements (TcPO 2 ) as a reference standard.…”
mentioning
confidence: 99%